Equitable and Holistic Public Health Measures During the Singaporean COVID-19 Pandemic - Samuel S. Y. Wang (Ubiquity Press, 2021)
This Covid-19 pandemic has been a trying time for all countries, governments, societies, and individuals. The physical, social, and organizational infrastructure of healthcare systems across the world is being stressed. This pandemic has highlighted that the healthcare of the country is as strong as its weakest link and that no aspect of life, be it social or economic, is spared from this pandemic. The authors would like to highlight some of the lessons learned from Singapore’s management of the Covid-19 pandemic. During the Singaporean Covid-19 pandemic, public health policy planning was all encompassing in its coverage, involving various stakeholders in government and society. The important role of individuals, governments, industry, and primary healthcare practitioners when tackling COVID-19 are highlighted. Singapore’s management of the Covid-19 pandemic involved an approach that involved the whole of society, with a particular focus on supporting the vulnerable foreign worker population, which formed the majority of Covid-19 cases in the country. Hopefully amidst the trying times, valuable lessons are learnt that will be etched into medical history and collective memory. We hope to highlight these lessons for future generations, both for members of the public and fellow healthcare practitioners.